Tetrahydroxydiboron‐Mediated Palladium‐Catalyzed Deoxygenative Transfer Hydrogenation of Aryl Ketones. Issue 15 (13th July 2022) - Spaller, William C.; Lu, Jennifer Q.; Stokes, Benjamin J.
Abstract: We describe a palladium‐catalyzed deoxygenative transfer hydrogenation of ketones using B2 (OH)4 as the sole additive. Deuterium labeling experiments using B2 (OD)4 show that the incorporated protons originate exclusively from the diboron reagent. Spectroscopic evidence implicates the intermediacy of a borate ester. A variety of aromatic ketones can be deoxygenated using this approach. Abstract :